Induction of ripening in 'rocha' pears subjected to low-temperature and ethylene application Indução do amadurecimento de peras 'Rocha' submetidas à baixa temperatura e à aplicação de etileno - de Martin M.S.* (2015)
The objective of this work was to evaluate the effect of the exposure to low-temperature and the application of ethylene, in different periods, on the ripening and quality of 'Rocha' pears. Two experiments were carried out. In experiment 1, four periods of exposure to 3° C (0, 14, 28, and 42 days) and the effect of the application of 100ppm of C2H4 for one and two days were evaluated. In experiment 2, five periods of exposure to 3°C were tested (0, 15, 30, 45, and 60 days). In experiment 1, increasing the period of low-temperature from 14 to 28 days brought about more yellowing to skin and increased respiratory rates and ethylene production. In all treatments, fruit had lower pulp firmness and lower strength to resist pulp penetration, in comparison to the control treatment; however, they showed buttery texture after seven days under environment conditions. In experiment 2, flesh firmness, strength to penetrate pulp, green skin, and titratable acidity decreased with the increase of the period under low-temperature. Fruit exposure to low-temperature at 3°C, for 15 days, and the application of 100ppm of C2H4, for two days, are indicated to induce ripening in 'Rocha' pears.